On the geometric side of the Arthur trace formula for the symplectic group of rank 2 - Hoffmann, Werner, 1959-; Wakatsuki, Satoshi, 1977- (Memoirs of the American Mathematical Society, 2018)
"We study the non-semisimple terms in the geometric side of the Arthur trace formula for the split symplectic similitude group and the split symplectic group of rank 2 over any algebraic number field. In particular, they express the global coefficients of unipotent orbital integrals in terms of Dedekind zeta functions, Hecke L-functions, and the Shintani zeta function for the space of binary quadratic forms."--Page v